Audit committees effecticeness and audit fees - Evidence from Chinese listed companies - Tian, Yakun (2019)
This paper explores the relationship between the effectiveness of audit committees and audit fees in China. The effectiveness of audit committees is measured by four separate proxies, independence, financial expertise, frequency of meetings and size as well as a composite variable of these four variables. This paper provides empirical evidence on this relationship by regressing 2655 observations (from 885 Chinese listed companies for three years). After controlling the board's and company's characteristics, it is found that the effectiveness has a positive and significant effect on audit fees. These results support the four hypotheses made. It indicates that high-quality audit committees perform monitoring duties more responsibly, which bring about wider audit scope, more audit work and higher audit fees. While after dividing 2655 observations into two groups (large-sized and small and medium-sized), financial expertise and size is positively but insignificantly related to audit fees in large size companies, independence and size is positively but insignificantly related to audit fees in small and medium size. Moreover, an additional robustness test is run to check whether the results will change or not when each year's data is regressed in isolation.